Pelatihan Implementasi Kurikulum Berbasis Cinta (KBC) bagi Guru Sekolah Dasar Se-Kota Mataram - Luluin Najwa; Mujiburrahman Mujiburrahman; M. Najamuddin; M. Chairul Anam (Jurnal Dedikasi Madani, 2026)
This community service program was carried out to improve elementary school teachers' understanding and implementation competency of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) issued by the Directorate General of Islamic Education, Ministry of Religious Affairs of the Republic of Indonesia, Decree No. 6077 of 2025. The training was held at SMA Negeri 6 Mataram and attended by elementary school teachers from across Mataram City. The background of this activity stems from the need to disseminate the KBC curriculum, which emphasizes the values of love toward Allah and the Prophet, knowledge, the environment, oneself and others, and the homeland as a foundation for character education in Islamic schools. The training was conducted through a participatory approach, covering conceptual understanding, curriculum mapping, lesson plan (RPP) development integrating KBC values, and practice-based learning strategies including Project-Based Learning and Experiential Learning. The results showed a significant increase in teachers' understanding of KBC concepts, improved ability to integrate love-based values into learning activities, and growing confidence in implementing student-centered and character-driven teaching. Teachers also reported that the KBC framework provided a structured and meaningful platform to address issues of intolerance, bullying, and environmental disregard in schools. Thus, this training has proven effective in strengthening teachers' capacity to implement the KBC curriculum and can be recommended for wider adoption across other educational units.